Distribution Analysis to Minimize Transportation Costs Using the Nearest Neighbor Method at PT. Unilever Indonesia Depo Makassar - Safira Amatullah, Fira; Lantara, Dirgahayu; Dahlan, Muhammad (Omnia Tempus, 2023)
Based on the problem formulation in this research, the goal that can be formulated in this research is to be able to distribute products using optimal distribution routes and minimize transportation costs at PT. Unilever Indonesia Makassar Depot. This research uses the Nearest Neighbor method approach to determine the shortest route so that the distribution path can be done optimally. Optimal means the amount of goods sent, delivery time, and the distance required is right, in this case there are many routes. Based on calculations carried out in completing the CVRP using the Nearest Neighbor method, the total distance traveled was 1,940.2 km. Meanwhile, the company's current total mileage is 2,348 km. This shows that the Nearest Neighbor method is effective in determining the distribution route for Sariwangi Tea at PT. Unilever Indonesia Makassar Depot. This research focuses on the distribution of goods from the company's depot (warehouse) to its customers. Delivery of goods involves services provided by the company within a predetermined time period to a number of customers using certain vehicles where the depot location can be at one or more locations. The results of this research provide input for future deliveries. It is hoped that companies can use new distribution routes using the Nearest Neighbor method, so that delivery costs can be controlled by using shorter or closest delivery routes and the costs are optimal. PT Unilever Indonesia is a subsidiary of Unilever which was founded in 1933. Having produced many well-known products, PT Unilever Indonesia is one of the large companies that contributes to meeting various community needs. As a company operating in the distribution sector, determining delivery routes is very important to consider time efficiency and minimize transportation costs.